Tribological properties of polymer like carbon coatings on NBG-18 nuclear graphite under nitrogen environment - HAN Hai; LIU Huichuan; CHENG Jinjuan; CHEN Xinchun; LIU Pengxiao; QI Wei; TANG Xian (He jishu)
BackgroundNuclear graphite coatings on the surfaces of spherical fuel elements in high-temperature gas-cooled reactors (HTGRs) exhibit a high friction coefficient and low wear resistance. The reciprocating movement of the fuel balls leads to significant friction among the spherical fuel elements and between these elements, the graphite bed, and other components. This friction generates a considerable amount of graphite dust, which poses a risk to the proper functioning of nuclear reactors.PurposeThis study aims to address the issues of friction and wear experienced by nuclear graphite on the surface of spherical fuel elements in HTGR by utilizing surface modification technology to enhance the mechanical and tribological properties of NBG-18 nuclear graphite.MethodsFirstly, NBG-18 graphite, sourced from SGL Group-The Carbon Company, Germany, was cut into blocks with dimensions of 20 mm×20 mm×5 mm, and a polymer-like carbon (PLC) coating was applied to NBG-18 nuclear graphite using a high-energy ion beam deposition (IBD) process with preprocessing of cleaning, sample loading, vacuuming, transition layer deposition, functional layer deposition, and sampling, resulting in a total coating thickness of approximately 400 nm. Subsequently, nanoindentation tests were conducted to determine the hardness and elastic modulus of the sample with a maximum load of 5 mN, while a high-load scratch tester was used to assess the film substrate adhesion of the coating. Then, the coefficient of friction (COF) of NBG-18 with the PLC coatings was examined in a nitrogen environment using a TRB3 friction tester at room temperature with specific testing parameters set for normal loads and sliding frequencies to identify the optimal conditions. Various analyses, including ultra-depth field microscopy, white light interferometry, and Raman spectrometry, were employed to study the microstructure, wear rate, and friction interface characteristics of the coated samples. Finally, comparisons were made between the surface morphology, mechanical properties, and tribological properties of the NBG-18 nuclear graphite before and after coating deposition, highlighting the enhancements brought about by the PLC coating. Simultaneously, the lubrication and failure mechanisms of the PLC coatings were investigated.ResultsThe experimental results demonstrate a significant increase in the hardness of NBG-18 nuclear graphite, from 0.44 GPa to 4.16 GPa, marking an 845% improvement post-PLC coating deposition. The elastic modulus rose from 9.00 GPa to 27.21 GPa, reflecting a 202% enhancement. The optimal conditions of a normal load of 2 N and a sliding frequency of 5 Hz led to a decrease in the friction coefficient from 0.335 7 to 0.006 5, a reduction of 98%. Moreover, the wear rate dropped from 3.71×10-3 mm3·(N·m)-1 to 1.81×10-6 mm3·(N·m)-1, representing a three-order-of-magnitude decrease. The mechanisms behind these improvements involve friction-induced graphitization of the PLC coatings and high hydrogen surface passivation, which play crucial roles in achieving ultra-smooth nuclear graphite. These findings provide valuable theoretical support for the advancement of surface-modified lubrication technologies for nuclear graphite.ConclusionsThe deposition of PLC coatings on the surface of NBG-18 nuclear graphite significantly enhances its friction and mechanical properties. These findings of this study provide valuable theoretical support for the advancement of surface-modified lubrication technologies for nuclear graphite.